Assessment of the Hydraulic Geometry of the Upper Meghna River in Bangladesh (Journal of Engineering Science, 2023)
The Meghna is one of the major rivers in Bangladesh. Frequent changes in flow and water level is a regular phenomenon due to the high seasonal rainfall variation. Such variations are exaggerated with cliamte change induced effects. Hence, it is crucial to figure out how climate change will affect the Meghna river's hydraulic properties. This study assesses water surface profile of a specific 120 km long reach of the Meghna river. A model was set up to run unsteady flow analysis for the years 2018, 2019, and 2020. The result matches well with the actual observation after calibration and validation. The study finds maximum water level during August, which mostly correlates with the high rainfall during this month of the monsoon season. The model has also been used to run a steady flow analysis for the return period of 2.33 years, 5 years, and 20 years. The result is useful for the sustainable design of bridges and other hydraulic structures.Journal of Engineering Science 13(2), 2022, 1-10